Tunisia : Teacher Policy - World Bank (Washington, DC, 2014)
A total of 1,995,167 students (around 96.2 percent of total enrollment) attend public schools in Tunisia. The public school student population is concentrated almost evenly between the primary (50.6 percent) and secondary levels (49.4 percent), and 82.6 percent of the total number of students attend schools in urban areas. Around 3.9 percent of enrolled students attend private schools (all of which are private, government- independent schools). All private schools are located in urban areas, principally serving secondary school students. Tunisia does have in place a mandatory probationary period prior to awarding open-ended status to new teachers. This may help in facilitating the dismissal of weak and unmotivated teachers earlier on, before they become permanent staff and part of the civil service. The first years of teaching are among the best available predictors of a teacher's performance later on. Therefore, it is positive to have in place screening processes to dismiss low-performing teacher entrants. In Tunisia, this screening process to gain open-ended status involves being assessed on performance. Once a teacher holds an open-ended appointment, the results of the performance evaluation process may be used in dismissing a teacher based on his/her performance. However, given the fact that data on the extent of teacher under-performance and rates of dismissal are unavailable, it is not possible to ascertain the extent to which ineffective teachers are removed in practice.